2023
DOI: 10.2147/jpr.s390386
|View full text |Cite
|
Sign up to set email alerts
|

Is Exercise Rehabilitation an Effective Adjuvant to Clinical Treatment for Myofascial Trigger Points? A Systematic Review and Meta-Analysis

Abstract: Purpose To systematically evaluate the effect of exercise rehabilitation as an adjuvant to clinical treatment for myofascial trigger points (MTrPs). Patients and Methods ESBCO, PubMed, Science Direct, Web of Science, China Knowledge Network (CNKI), and Wanfang databases were comprehensively searched from database inception date through July 2022. Randomized controlled trials comparing MTrPs treatments that included exercise rehabilitation with a single clinical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Our results showed that focal ESWT and mesotherapy are two valuable therapeutic proposals in the management of patients with myofascial pain syndrome. In fact, the treatment of myofascial syndrome is multimodal; we make use of pharmacological therapy (anti- inflammatories, muscle relaxants, local anesthetics, antidepressants and weak opioids), ( 14 , 15 ) often in association with rehabilitative treatment with active and constant exercise, stretching exercises and postural rehabilitation ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that focal ESWT and mesotherapy are two valuable therapeutic proposals in the management of patients with myofascial pain syndrome. In fact, the treatment of myofascial syndrome is multimodal; we make use of pharmacological therapy (anti- inflammatories, muscle relaxants, local anesthetics, antidepressants and weak opioids), ( 14 , 15 ) often in association with rehabilitative treatment with active and constant exercise, stretching exercises and postural rehabilitation ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of myofascial syndrome is varied and heterogeneous; pharmacological therapy with muscle relaxants, antidepressants, weak opioids, local anesthetics, and anti-inflammatories taken orally or topically (in the form of a patch or by mesotherapy) is often used for the management of algic symptoms and painful “PTs” ( 14 , 15 ). Rehabilitative treatment with active and constant exercise is an effective strategy in the treatment of myofascial pain: it improves joint ROM, mood, and pain threshold, promoting a better quality of life for patients; one of the prescribed exercises is stretching, which stretches myofascial compartments containing PTs and prevents their further occurrence; postural rehabilitation is another rehabilitation option ( 16 ). Patients also often undergo massage therapy and manual therapy sessions.…”
Section: Introductionmentioning
confidence: 99%